Extremal Vectors for a Class of Operators - Downey, Larry; Ong, Boon W. (Sarajevo Journal of Mathematics, 2024)
In this note, we study extremal vectors for a class of operators with a special application to the the Volterra operator. The study requires the description of the asymptotic behavior of a class of infinite series involving a real parameter. 2000 Mathematics Subject Classification. 47A05, 40C99